A sister of NANOG regulates genes expressed in pre-implantation human development - Dunwell, T; Holland, P (Royal Society, 2017)
The NANOG homeobox gene plays a pivotal role in self-renewal and maintenance of pluripotency in human, mouse and other vertebrate embryonic stem cells, and in pluripotent cells of the blastocyst inner cell mass. There is a poorly studied and atypical homeobox locus close to the Nanog gene in some mammals which could conceivably be a cryptic paralogue of NANOG, even though the loci share only 20% homeodomain identity. Here we argue that this gene, NANOGNB (NANOG Neighbour), is an extremely divergent duplicate of NANOG that underwent radical sequence change in the mammalian lineage. Like NANOG, the NANOGNB gene is expressed in preimplantation embryos of human and cow; unlike NANOG, NANOGNB expression is restricted to 8-cell and morula stages, preceding blastocyst formation. When expressed ectopically in adult cells, human NANOGNB elicits gene expression changes, including down-regulation of a set of genes that have an expression pulse at the 8-cell stage of pre-implantation development. We conclude that gene duplication and massive sequence divergence in mammals generated a novel homeobox gene that acquired new developmental roles complementary to those of Nanog.